Fatores associados ? condi??o bucal e ? infec??o pelo HIV/AIDS - Souza, Anderson Jambeiro de (2013)
After the discovery of the Human Immunodeficiency Virus (HIV), in the 1980s, the clinical and epidemiological characteristics of Acquired Immunodeficiency Syndrome (AIDS) have changed over the years, mainly from the second half of the 1990s, with the emergence of new drugs for its treatment. Objective: to investigate the oral condition and the HIV infection condition factors associated in individuals living with HIV/Aids. Method: a cross-sectional, descriptive, exploratory study. Single examiner used a data collection instrument in Assistance Specialized Services (SAE - STD/HIV/Aids) users in three municipalities in the Bahia State. The information derived from primary data (interviews and oral clinical examination) and secondary data (clinical records). Socio-demographic, lifestyle and health condition characteristics, HIV/Aids infection and oral condition were researched. Individuals registered in these services, with age greater than or equal to eighteen years old, gender both and that participate accepted voluntarily in the research were evaluated. Sample size was determined by convenience, from the data collection availability time. For statistical analysis, the Stata 10 statistical package used, the Chi-square test was used for categorical variables, with 5% significance level. Results: preliminary results in 228 individuals showed that the majority was male gender, browns, with a mean age 41.6 years old and the average HIV infection diagnosis time was 5.4 years. The HIV/Aids infection condition, as assessed by CD4 T-lymphocyte count showed statistically significant association with: current occupation, antiretroviral drugs use duration, last viral load determination and intra-oral injury presence. As for the oral condition, in relation to dental caries, the following factors significantly associated: age, race, current occupation, family income, average number of cigarettes per day, total and / or partial prosthesis use, prosthesis dental use, gingivitis and flossing. For intra-oral lesion presence was associated with age, educational level, current smoking, antiretroviral medications duration, dosage last viral load last count CD4 + T lymphocytes, CD4/CD8 ratio, gingivitis , periodontitis and flossing. Regarding the periodontitis, the following factors were associated: sex, residence county, past smoking, current smoking and flossing. Conclusions: the preliminary findings point to association between socio-demographic, lifestyle characteristics and HIV infection condition and oral condition, suggesting the need for better understanding of the influence of these variables in the individuals living with HIV/Aids monitoring, contributing to preventive measures, treatment and survival of the infection diagnosed individuals.